2011
DOI: 10.1016/j.jmb.2010.10.030
|View full text |Cite
|
Sign up to set email alerts
|

A New Clustering of Antibody CDR Loop Conformations

Abstract: Previous analyses of the complementarity determining regions (CDRs) of antibodies have focused on a small number of “canonical” conformations for each loop. This is primarily the result of the work of Chothia and colleagues, most recently in 1997. Because of the widespread utility of antibodies, we have revisited the clustering of conformations of the six CDR loops with the much larger amount of structural information currently available. In this work, we were careful to use a high-quality data set by eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
540
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(559 citation statements)
references
References 37 publications
11
540
2
Order By: Relevance
“…In contrast, chickens use a much longer V H CDR3 repertoire and frequently stabilize these long binding loops by introducing non-canonical disulfide bonds (32). In the structure presented here, a descriptive example of that mechanism is highlighted, along with a V CDR1 structure, which may be common in chicken antibodies but is distinctly different from any hitherto described structure in mammals (58,69).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In contrast, chickens use a much longer V H CDR3 repertoire and frequently stabilize these long binding loops by introducing non-canonical disulfide bonds (32). In the structure presented here, a descriptive example of that mechanism is highlighted, along with a V CDR1 structure, which may be common in chicken antibodies but is distinctly different from any hitherto described structure in mammals (58,69).…”
Section: Discussionmentioning
confidence: 86%
“…We therefore systematically compared the CDR sequences and conformations of this clone with the canonical CDRs from humans and rodents as classified by North et al (58). CDR-H3 was not included in the analysis because it is known to have diverse lengths and structures (58). We found that chicken CDR-L2, CDR-L3, CDR-H1, and CDR-H2 all adhere to canonical conformations seen in mammalian structures and could be classified into clusters L2-8, L3-11, H1-13, and H2-10, respectively (58).…”
Section: X-ray Crystallographic Analysis Of How Antibody Pt231/ Ps235mentioning
confidence: 95%
See 1 more Smart Citation
“…The black vertical lines are mutations in dC on either strand and are presumed to have been initiated by the direct action of AID, whereas the gray vertical lines are mutations in A:T residues and are presumed be a result of error-prone MMR (47). After recent precedents (1,30,48), the CDRs indicated by the horizontal gray bars at the top of the figure are based on the Kabat criteria (49) combined with analysis of the crystal structure of the IGHV3-23*01 V region, rather than the IMGT definition (48). It is obvious that the frequency of these independent and unique somatic mutations in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Antibodies can do this, too, but they can also bind to an unstructured terminal peptide or long loop, which adapts to a pocket or groove between the antibody variable domains. Conversely, the complementary determining regions (CDRs) of the antibody, especially a long CDR-H3, can bind within a pocket of the target or at the side of a domain (69). The preference of DARPins for recognizing structural components could be advantageous in selecting HIV envelope-directed inhibitors, particularly as recent findings of potent broadly active neutralizing antibodies revealed a high prevalence of antibodies recognizing conformational inter-and intraprotomer loop-spanning binding domains (70,71).…”
Section: Discussionmentioning
confidence: 99%